Indigenous healing and the making of medical knowledge in colonial Java - Ningsih, Widya Fitria; Ariwibowo, Gregorius Andika; Budiman, Hary Ganjar Budiman; Fibiona, Indra (Medicina Historica, 2026)
This article examines how indigenous healing in colonial Java became a site of epistemic negotiation, shaped by the asymmetrical power of colonialism. Rather than offering a descriptive account of dukun and jamu, the study analyses how colonial physicians and botanists represented, classified, and selectively incorporated local practices into emerging medical categories. The article addresses a key gap in existing scholarship by examining how indigenous medical expertise was reframed through colonial epistemologies, rather than documented from local perspectives. Using a qualitative historical approach, the study treats colonial medical and botanical publications as situated archives shaped by interpretive bias and uneven authority. This analytical lens reveals how dukun were positioned simultaneously as sources of empirical material and as objects of marginalizing discourse, and how jamu was redefined from a holistic socio-cosmological practice into a regulated category of “native remedies.” The article argues that indigenous healing persisted under colonial rule and became embedded, often in subtle ways, in the formation of hybrid medical knowledge in the Indies. This focus on epistemic negotiation contributes to debates on colonial science and epistemic mediation and offers an approach for reconstructing indigenous epistemologies from within uneven archives.